Tribal church: ministering to the missing generation - Merritt, Carol Howard (Alban Institute, 2007)
Tribal church -- Fostering intergenerational relationships -- Encouraging economic understanding -- Cultivating unambiguous inclusion -- Discovering affirming traditions -- Promoting shared leadership -- Nurturing spiritual community -- Growing life